Circulating Lymphocyte Subsets Induce Secondary Infection in Acute Pancreatitis - Ding, Lili; Yang, Yimin; Li, Hongxiang; Wang, Haijiao; Gao, Pujun (Frontiers in Cellular and Infection Microbiology, 2020)
Acute pancreatitis (AP) is considered as a cascade of immune responses triggered by acinar cell necrosis. AP involves 2 main processes of systemic inflammatory response syndrome and subsequent compensatory anti-inflammatory response syndrome. Although great efforts have been made regarding AP therapy, the mortality rate of AP is still high. Secondary infection acts a lethal factor in AP. Lymphocytes act as major immune mediators in immune responses in the course of this disease. However, the relationship between lymphocytes and secondary infection in AP is unclear. This review summarizes the variation of lymphocytes and infection in AP. Knowledge of the characterization of circulating lymphocyte abnormalities is relevant for understanding of the pathophysiology of AP.